KONSENTRASI PASIR BESI TITAN DARI PENGOTORNYA DENGAN CARA MAGNETIK - Sufiandi, Deddy (Jurnal Metalurgi, 2011)
Titan iron sand has been found a lot in Indonesia especially around west coast of Java. One of titan iron sand used in this research is iron sand from Tegal Buleud area at Sukabumi west coast. The utilization of iron sand is an alternative to fill-up the rising demand of raw material for steel industry development due to limited amount of conventional iron ore. To obtain the quality of titan iron sand which is suitable with the requirement for smelting, it is needed to have concentration process by magnetic separator to increase iron content. The step of experiment were identification of titan iron sand composition, preparation of sample and sampling processes, and material separation using magnetic separator to get concentrate, middling, and tailing products. The result of experiment shown concentrate product of titan iron sand has Fe2O3 and TiO2 with weight composition 80 % and 20 % respectively. And also The optimum condition in magnetic separator was 3.5 Ampere current and fraction -100 mesh got average concentrate yield about 90 %.